La biodiversité dans des territoires insulaires, approche théorique et perspectives de développement - Jean-Raphaël Gros-Désormeaux (Développement Durable et Territoires)
The increase in the needs for space and natural resource threatens the existence of the current biosphere with incurable changes in the composition and the structuring of its biological diversity. The inventory of the relations between man and biodiversity emphasizes the extinction of a certain number of species specific. Facing the irreversible effects of hunting and the destruction of biotopes, land-use planning and economic development of the insulars territory tend to be conceived by taking into account sustainable management integrating world diversity : that is the biodiversity in its broadest meaning. Thus, the avian species of Martinique are conceived as biological entities to be preserved but much more still like pretexts in the protection and valorization of some biospatials unit, particularly for recreation purposes.